1974
DOI: 10.1021/jo00919a020
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of cephalotaxus harringtonia var drupacea. 11-Hydroxycephalotaxine and drupacine

Abstract: Melting points were taken on a Kofler hot stage and are uncorrected. Infrared spectra were determined in KBr disks with a Perkin-Elmer Model 21 spectrophotometer and ultraviolet spectra were determined in ethanol with a Carey Model 17 spectrophotometer. Nuclear magnetic resonance spectra were recorded on a Varían A-60A spectrometer using tetramethylsilane as internal reference and CDCI3 as solvent unless otherwise indicated. Mass spectra were determined by Morgan-Schaffer Corp., Montreal, on a Hitachi Perkin-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 7 publications
0
51
0
Order By: Relevance
“…Its UV absorption bands at 203 and 291 nm and IR absorption bands at 3520, 3406, 1631, 1500, 1482, 1342 cm −1 were consistent with those of Cephalotaxus alkaloids [2]. Analysis of the 1 H and 13 C NMR data of 1 (Tables 1, 2) revealed several typical functionalities similar to those of the known alkaloid drupacine ( 6 ) [2], including a tetrasubstituted benzene ring with two para H-atoms ( δ H 6.76, δ C 110.1; δ H 6.72, δ C 106.0; δ C 128.6, 132.4, 146.8, 147.4), a –OCH 2 O– moiety ( δ H 5.97; δ C 101.5), a ketal carbon ( δ C 106.7), two O -bearing CH groups ( δ H 3.86, δ C 76.7; δ H 4.81, δ C 76.1), and two –OH groups ( δ H 3.53 and 4.68). The molecular formula of 1 was established as C 17 H 19 NO 5 with nine degrees of unsaturation by HRESIMS ([M+H] + at m/z 318.1336), absence of a methyl than that of 6 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Its UV absorption bands at 203 and 291 nm and IR absorption bands at 3520, 3406, 1631, 1500, 1482, 1342 cm −1 were consistent with those of Cephalotaxus alkaloids [2]. Analysis of the 1 H and 13 C NMR data of 1 (Tables 1, 2) revealed several typical functionalities similar to those of the known alkaloid drupacine ( 6 ) [2], including a tetrasubstituted benzene ring with two para H-atoms ( δ H 6.76, δ C 110.1; δ H 6.72, δ C 106.0; δ C 128.6, 132.4, 146.8, 147.4), a –OCH 2 O– moiety ( δ H 5.97; δ C 101.5), a ketal carbon ( δ C 106.7), two O -bearing CH groups ( δ H 3.86, δ C 76.7; δ H 4.81, δ C 76.1), and two –OH groups ( δ H 3.53 and 4.68). The molecular formula of 1 was established as C 17 H 19 NO 5 with nine degrees of unsaturation by HRESIMS ([M+H] + at m/z 318.1336), absence of a methyl than that of 6 .…”
Section: Resultsmentioning
confidence: 84%
“…Six methylenes, 3 methines, a methyoxyl and 5 quaternary carbons in the 13 C NMR spectrum of alkaloid 5 revealed that 5 belongs to homoerythrina-type alkaloids rather than cephalotaxine-type alkaloids [2]. The 13 C NMR and DEPT data of alkaloid 5 were similar to those of comosine ( 18 ) [21] with exception for three downfielded signals [87.0 (s), 67.6 (t), 63.3 (t)], suggesting a N -oxide moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the bark has long been used in TCM for various indications. Powell et al (59)(60)(61) originally isolated the antitumor alkaloids homoharringtonine (E1) and harringtonine (E2). Subsequently, Chinese investigators discovered that alkaloids from C. fortunei Hook.…”
Section: Cephalotaxus Speciesmentioning
confidence: 99%
“…5 Compounds from Cephalotaxus species various indications. Chinese investigators[63] discovered the antitumor properties of alkaloids from C. fortunei Hook., subsequent to Powell's[64][65][66] original isolation of the antitumor alkaloids homoharringtonine (E1) and harringtonine (E2). The Chinese evergreen tree C. harringtonia K. Koch var.…”
mentioning
confidence: 99%